Steady states with unbounded mass of the Keller–Segel system. Issue 1 (30th January 2015) - Pistoia, Angela; Vaira, Giusi
Abstract : We consider the boundary-value problem where B r 0 is the ball of radius r 0 in ℝ N, N ≥ 2, λ > 0 and ν is the outer normal derivative at ∂ B r 0 . This problem is equivalent to the stationary Keller—Segel system from chemotaxis. We show the existence of a solution concentrating at the boundary of the ball as λ goes to 0.